Direct transatrial implantation of balloon-expandable valve for mitral stenosis with severe annular calcifications: early experience and lessons learned. (26th July 2017) - El Sabbagh, Abdallah; Eleid, Mackram F; Foley, Thomas A; Al-Hijji, Mohammed A; Daly, Richard C; Rihal, Charanjit S; Said, Sameh M
Abstract: OBJECTIVES: Patients with symptomatic severe mitral annular calcification present a therapeutic challenge. Direct transatrial implantation of SAPIEN valve has emerged as an alternative to surgical mitral valve (MV) replacement for high-risk surgical candidates. METHODS: This series includes 6 consecutive patients with symptomatic severe mitral annular calcification deemed to be at high risk for standard surgery. All patients underwent direct transatrial implantation of balloon-expandable SAPIEN valve in the mitral position. RESULTS: Mean age was 81 years [3 (50%) female], with an average Society of Thoracic Surgeons score of 10.3%. All patients had at least New York Heart Association Class III symptoms. Procedure was performed using normothermic cardiopulmonary bypass. The MV was approached through a standard left atriotomy in 4 patients and via a vertical trans-septal approach in the remaining 2 patients. Resection of the anterior leaflet of the MV was performed in 4 patients. The valve was successfully deployed in all patients. The diastolic mean gradient across the MV decreased from an average of 14 ± 3 to 5 ± 1 mmHg post deployment. There was no left ventricular outflow tract obstruction. MV periprosthetic regurgitation was severe in 3 patients and moderate to severe in 1 patient. In-hospital mortality occurred in 3 (50%) patients due to a non-cardiac cause in 1 patient and cardiogenic shock in the other 2 patients. CONCLUSIONS: Early experience with direct transatrial balloon-expandable implantation for severe mitral annular calcification revealed feasibility of this approach but significant morbidity and mortality primarily related to periprosthetic regurgitation that requires further refinement of the technique.